Terahertz microfluidic sensing with dual-torus toroidal metasurfaces - Xu, Jinjin (2022)
Toroidal excitation manifests as currents flowing on the surface of a torus along its meridians that are known as poloidal currents. Several intriguing phenomena such as nonradiating anapole excitation, dynamic Aharonov–Bohm effect, and vector potential in the absence of electromagnetic fields occur in the presence of toroidal excitations. Toroidal resonances in metamaterials also offer a platform to probe strong light–matter interactions in its proximity due to the nonradiating confinement of photons. Here, a dual-torus toroidal flexible metasurface containing an array of overlapped split ring resonators is experimentally demonstrated, which results in strong field confinement for enhanced sensing of polar liquid analytes. Microfluidic integrated dual-torus toroidal resonance experimentally shows significantly higher sensitivity of 124.3 GHz per refractive index unit compared to a single torus toroidal resonance. Flexible metasurfaces supporting dual torus toroidal resonance can find a wide range of applications in the development of ultrasensitive terahertz molecular sensors for probing real time monitoring of chemicals and biomolecules.